Governmental policy capacity and policy work in a small place: Reflections on perceptions of civil servants in Prince Edward Island, Canada from a practitioner in the field - Cameron, Bobby Thomas Robert (FIA UB, 2020)
The body of public administration literature is missing contributions from practitioners in the field. Emic or insider-led studies of public administration can act as powerful mechanisms to generate new knowledge. This article studies the relationship between place, perceptions and policy work by drawing on the author’s own public administration experience and interviews with civil servants. The results show that societal factors such as political culture and reduced anonymity associated with small place create challenges when developing public policy. However, expedited public engagement and problem identification were perceived by civil servants to be enhanced by a small context. This means that small place can be both limiting and beneficial for high levels of policy capacity. Overall, this article finds that geospatial factors such as smallness impact perceptions of policy work and capacity. Furthermore, this article finds that insider-led studies of public administration can indeed make important and unique contributions to the body of literature and are therefore deserving of more serious methodological consideration.